The Influence of Policy Implementation, Budgeting, Human Resource Competency, and Public Service Quality on Information Transparency at The Coordinating Ministry for Political, Legal, and Security Affairs of The Republic of Indonesia - Indarto, Eko Dono (Indonesian Journal of Multidisciplinary Science, 2026)
This study aims to analyze and determine the influence of Policy Implementation, Budgeting, Human Resource Competence and Public Service Quality on Information Disclosure of the Coordinating Ministry for Political and Security Affairs of the Republic of Indonesia both partially and together. The sampling technique in this study is proportional stratified random sampling with a sample of 75 respondents. This research method is included in the type of explanatory research that uses a quantitative approach. Data collection techniques use documentation techniques, literature studies, questionnaires and observations. The data collection tool for this study is a questionnaire based on the Likert scale. The data analysis techniques in this study are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, F test and t test, simple and multiple linear regression. The results of the study prove that there is a positive and significant influence, both partially and together, First, the implementation of policies on Information Disclosure is 62.2%. Second, there is an effect of Budgeting on Information Disclosure of 55.2%. Third, there is an influence of Human Resource Competence on Information Disclosure of 65.6%. Fourth, there is the Influence of Public Service Quality on Information Disclosure by 68.9%. And fifth, there is the influence of Policy Implementation, Budgeting, Human Resource Competence and Public Service Quality together on Information Disclosure of 92.3% which has a very large and positive effect.